Corrigendum to "Existence of solutions for a quasilinear elliptic system with local nonlinearity on ℝN$$ {\mathbb{R}}^N $$" [Math. Meth. Appl. Sci., 2021, 44(17): 13186–13212]. (17th May 2022) - Zhang, Xingyong; Liu, Cuiling
Abstract : We would like to correct the range of r i ( i = 1, 2 ) $$ {r}_i\left(i=1, 2\right) $$ in the condition (F2) of Theorem 1.1 and an error (i.e., the proof of inequality (3.16)) in the proof of Lemma 3.4 in [Math. Meth. Appl. Sci., 2021, 44(17): 13186–13212].